Radiological predictors of PCP in HIV-positive adults in South Africa: a matched case-control study - Wills, Nicola (Department of Medicine, 2025)
Definition of chest X-ray (CXR) features associated with laboratory-confirmed pneumocystis pneumonia (PCP) among HIV-positive adults is needed to improve diagnosis in high-burden settings. Methods: We conducted a case-control study involving HIV-positive adults with laboratory-confirmed PCP and a matched cohort with non-PCP respiratory presentations at regional hospitals in Cape Town, South Africa (2012 – 2020). The primary objective was to identify CXR features associated with confirmed PCP diagnosis and severe PCP (defined by hypoxia, ICU referral/admission, and/or in-hospital death). We explored the performance of logistic regression models, incorporating selected clinical and CXR predictors, for PCP diagnosis and severe PCP. Results: Records from 104 adults (52 PCP cases and 52 non-PCP controls) were included. Diffuse versus patchy ground glass opacification was associated with increased odds of PCP diagnosis (adjusted odd's ratio (aOR) 6.2, 95% confidence interval (CI) 1.6 – 28.9, p =0.01) and severe PCP (aOR 4.5, 95%CI 1.6 – 14.4, p =0.008). Consolidation was associated with severe PCP (aOR 3.3, 95%CI 1.2 –11.0, p =0.03) as was increasing ground glass zone involvement (aOR 2.1 for each one-unit increase in involved zone; 95% CI, 1.4 – 3.2, p = 0.0004). Models incorporating hypoxia (hypoxia model) or tachypnoea (respiratory rate model) with diffuse ground glass opacities, absence of pleural effusion or reticular/reticulonodular changes on CXR performed well in predicting PCP (area under the receiver operating characteristic curve 0.828 (hypoxia model) and 0.857 (respiratory rate model). Conclusions: CXR evaluation alongside bedside clinical information offers good accuracy for discriminating definite PCP from other HIV-associated respiratory diseases.